War, Woman, and Environment: An Ecofeminist Reading of A Thousand Ships by Natalie Haynes - Merve Altın (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi, 2025)
This study aims to offer an ecofeminist reading of Natalie Haynes’ novel A Thousand Ships (2019) to analyse how the text reflects and critiques the intersections of militarism, gendered violence, and environmental destruction. Ecofeminism, as a critical and interdisciplinary approach, reveals the relationships between the oppression of women and the degradation of nature, both of which are argued to stem from patriarchal and capitalist structures. While the novel does not explicitly aim to explore such themes as war, heroism, and gender within ecological frameworks, it inevitably highlights the interconnected nature of these themes. Through women’s narratives and the narrative of Gaia, the Earth Goddess, the novel reflects how patriarchal and capitalist systems exploit both women and the environment. The study also draws parallels between the Trojan women’s experiences and contemporary conflicts, such as those in Gaza and Ukraine, where women, children, and nature are disproportionately affected by war, as reflected in official reports prepared on these issues for the respective regions. By situating A Thousand Ships within an ecofeminist context, therefore, this study demonstrates how literature can reflect and critique the ongoing and universal nature of women’s suffering and environmental degradation and highlights their interconnectedness due to the pervasive influence of patriarchal and capitalist practices. Such an approach not only expands the existing scholarship but also emphasises the importance of understanding and addressing these issues in both historical and contemporary contexts.